The correlation between antropometric indices and lipid profile indices among Malay obese attributes - Atif, Amin Baig; Nordin, Simbak; Muhammad Ilyas, Nadeem; Muhammad Umer, Khan (2018)
Obesity is representation of an excessive fat accumution in enlarged adipose tissues in the body that results in decreased physical activity. Obesity etiopathology is influenced by genetic and environmental factors besides that obesity is associated with cardiovascular disorder. This cross-sectional study aimed to determine correlation of anthropometric indices with lipid profile indices among Malay obese people. A total of 193 subjects were included from Terengganu in this study as per inclusion criteria. The anthropometric measurements; [body mass .index (BMI). waist circumference (WC). hip circumference (HC). waist to hip ratio (WHR). waist to height ratio (WHLR), abdominal volume Index (AVI), con icity index (CI)], and associated lipid profile indices; [triglyceride (TG), total cholestrol (TC), HDL, LDL, TG/HDL, and LDL/HDL] of the subjects were calculated. Besides descriptive analysis of age, gender, anthropometric measurements and lipid profile's means were determined and correlation analysis was performed using Pearson's correlation. The mean age values for obese were male 39.20 ± 8.70 and fcm ale 41.08± 1.01, and for non-obese were male 29.82 ± 1.27 and female 33.28 ± 1.25. The comparison of the means or anthropometric measurement and lipid profile has shown significant results between both groups. Results indicated that TG showed good correlation with WC (r=0.420), WHR (r=0.500 and AVI (r=0.407), while TG/HDL has also shown good correlation with WC (r=0.437), WHR (r=0.489) and AVI (r=0.426). ln conclusion. the lipid profile (TG and TG/J IDL) significantly correlates with anthropometric measurements (WC.WHR, and AVI), which indicates obesity related cardiac risk factors.